Analisis Pengaruh Kompetensi, Integritas, Pelayanan Prima, Dan Intelektualitas Sumber Daya Manusia Terhadap Kinerja Pegawai PT. Bank Central Asia Dikota Makassar - Tamanyira, Yuliatti; Mas’ud, Masdar; Azis, St. Nurhayati (Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the factors that influence employee performance. These factors consist of competence, integrity, excellent service, and intellectuality. The data used in this study are primary data obtained directly from respondents using a questionnaire of 50 respondents with the Likert scale calculation method. The respondents selected in this study were BCA customers in Makassar City. The analysis method used is multiple linear regression with the SPSS analysis tool by first transforming from ordinal numbers to interval numbers through the Successive Interval Method (MSI). Based on the analysis that has been carried out, the results obtained are that partially the competence and excellent service variables have a positive and significant effect while the integrity and intellectuality variables do not have a significant effect on employee performance. It can be said that in this study there are two variables, namely competence and excellent service, which have a significant influence together on employee performance variables with a percentage level of 65%, while the remaining 35% is influenced by other variables. Keywords: Employee Performance, Competence, Integrity, Excellent Service, Intellectuality, Bank Central Asia, Successive Interval Method